The effects of water vapour on the hot corrosion of gas turbine blade materials at 700 °C - Potter, Andrew; Sumner, Joy; Simms, Nigel J. (Taylor & Francis, 2022)
Future developments in power generation are likely to require gas turbines to operate in novel combustion environments. The level of water vapour in the turbine’s gas stream is one variable that may change as a consequence. This paper explores the effects of water vapour on hot corrosion. The ‘deposit recoat’ technique was used to evaluate the hot corrosion performance of superalloys PWA 1483 and MarM 509 in atmospheres containing between 0 and 20 vol.% water vapour. Exposures were carried out at 700 °C in atmospheres containing 300 ppm SO2 for up to 500 hours. The deposit was an 80% Na2SO4, 20% K2SO4 solution applied with a deposition flux of 1.5 µg/cm2/h. The findings are compared to similar exposures with 3.6 ppm SO2. Increasing levels of water vapour were observed to reduce sound metal loss in atmospheres containing 300 ppm SO2 while increasing sound metal loss in atmospheres containing 3.6 ppm SO2.
Keywords: Type II hot corrosion; superalloys; water vapour; mixed mode hot corrosion